Antimicrobial prophylaxis in management of urinary tract stones by extracorporeal shock-wave lithotripsy: is it necessary? - KORTEN, VOLKAN (My University, 1995)
OBJECTIVES: In a prospective randomized study, we evaluated the incidence of urinary tract infections following extracorporeal shock-wave lithotripsy (ESWL) and the necessity of prophylactic antibiotic administration in patients treated with this modality. METHODS: A total of 360 consecutive patients with renal and ureteric stones who had sterile urine before ESWL treatment and did not have any increased risk of infection received either a single dose of 400 mg of ofloxacin or no prophylaxis. Patients were followed by simple urine analysis and urine cultures together, with clinical evaluations. RESULTS: Only 3 patients (0.8%) had positive urine cultures at 1 week after ESWL. Two of these patients were in the antibiotic prophylaxis group. CONCLUSIONS: The incidence of urinary tract infections after ESWL is extremely low, provided that patients have sterile urine before ESWL, and prophylactic antibiotics are not required.
Keywords: Adult; Female; Humans; Male; Risk Factors; Incidence; Prospective Studies; Premedication; Ofloxacin; Lithotripsy; Bacteriuria; Ureteral Calculi; Kidney Calculi